CLOFFAR - update 1 - supplement to Checklist of the Freshwater Fishes of Argentina - Koerber, Stefan (2015)
Despite the fact that this first update of CLOFFAR contains 15 changes, the number of species has increased by only 4. The main driver for the recent changes is the paper of Thomaz et al., proposing 8 new combinations for stevardiine characiforms. In addition, 2 new Crenicichla and first records for a tachuela, a pejerrey, and a heptapterid have been published. The latter also resulted in the negative account for another heptapterid, erroneously determined before, increasing the number of freshwater fish species known from Argentina to 519.